Going Deeper into Profound Learning through Intellectual Humility, Deep-Surface Learning, and Bildung - Michael Kroth; Laila Cornwall; George Watson (Adult Education Research Conference, 2018)
Profound learning (PL) has recently been introduced as a possible approach and process for lifelong learning. Here, we look through the lens of Bildung, deep-surface learning, and intellectual humility to elaborate this developing construct.
Keywords: Profound learning; Bildung; deep-surface learning; intellectual humility